Penerapan Model Pembelajaran Sains Teknologi Masyarakat dan Pengaruhnya Terhadap Hasil Belajar ditinjau dari Kemampuan Matematis - Hafidz Hafidz; Nanik Suhernawati; Rafif Addarquthni (Program Studi Pendidikan Matematika IKIP PGRI Jember, 2019)
So far there is still a growing view that social and scientific scientific development are two separate entities. Science and social work in different directions even across from shared values. Interest in developing science sometimes does not consider the needs and desires of the community as a representation of the social realm, and vice versa. Learning with the Community Technology Science model will provide solution answers to scientific and social ego issues so that they will hack into the relationship between the two. The Community Technology Science learning model will present learning that instills an understanding that between science and social must go together, the development of science must answer the needs and interests of society. This study tries to apply the Science Technology Community learning model with a review of the mathematical ability of its influence on learning outcomes. This study uses a hypothesis test (T test) using a statistical program and is a type of quantitative causality research. The research locations were Ambulu SMPN 2 and Rambipuji 2 Public Middle School with respondents as students of the two schools.